Hypocholesterolemic neutraceutical oil. - Ismail, Maznah; Abdullah, Abdul Salam; Azlan, Azrina (2004)

(untitled)
The present invention relates to edible oil with excellent fatty acid profile, improved antioxidants contents and stability. The edible oil of the present invention is health oil with hypocholestrolemic and nutraceutical potential as it is improves the total antioxidant status, enhances lipid peroxidation, and reduces LDH/HDL ratio and decrease the risk of coronary heart disease (CHD) of human subjects. The nutraceutical oil of the present invention is a mixture of rice bran oil and palm oil in appropriate portion that finally produces the nutraceutical oil with about 70-80% of fatty acids; about 900-1200ppm of any one or combination of tocopherol and tocotrienol; about 900-1200ppm of Vitamin E; and about 10000-10400ppm of oryzanol.